2015
DOI: 10.1088/0004-637x/806/2/214
|View full text |Cite
|
Sign up to set email alerts
|

LABORATORY MEASUREMENTS OF WHITE DWARF PHOTOSPHERIC SPECTRAL LINES: Hβ

Abstract: We spectroscopically measure multiple hydrogen Balmer line profiles from laboratory plasmas to investigate the theoretical line profiles used in white dwarf atmosphere models. X-ray radiation produced at the Z Pulsed Power Facility at Sandia National Laboratories initiates plasma formation in a hydrogen-filled gas cell, replicating white dwarf photospheric conditions. Here we present timeresolved measurements of Hβ and fit this line using different theoretical line profiles to diagnose electron density, n e , … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 60 publications
3
46
0
Order By: Relevance
“…The latter is evident for high order lines (n f > 5), in which the red wing falls quickly for the quasi-molecular profile, while the red wing in the electronic Stark behaves similarly to the blue wing and decreases slowly. These differences may be the cause of the inconsistent densities reported by Falcon et al (2014) and Genest-Beaulieu & Bergeron (2014), which are obtained when different lines are fitted.…”
Section: Comparison To Electronic Starkmentioning
confidence: 93%
See 3 more Smart Citations
“…The latter is evident for high order lines (n f > 5), in which the red wing falls quickly for the quasi-molecular profile, while the red wing in the electronic Stark behaves similarly to the blue wing and decreases slowly. These differences may be the cause of the inconsistent densities reported by Falcon et al (2014) and Genest-Beaulieu & Bergeron (2014), which are obtained when different lines are fitted.…”
Section: Comparison To Electronic Starkmentioning
confidence: 93%
“…Hence the inconsistencies between the spectroscopic method and other methods are reduced when corrections to 3D convection are applied, but are still without a complete solution at present (Genest-Beaulieu & Bergeron 2014). Falcon et al (2014) noted that the inferred electronic density of a plasma when fitting H γ was ∼ 40 % smaller than the density obtained when fitting H β, regardless of the set of models used. They suggested that this inconsistency would lead to lower determinations of surface gravities and, by consequence, a lower mean mass would be obtained.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Calculations of spectral line broadening are important for a variety of applications, including diagnosing laboratory plasma conditions [1,2], determining temperatures and gravities of white dwarf stars [3], and calculations of stellar opacities [4]. The accuracy of line-broadening calculations is determined by several factors: the accuracy of the atomic structure, the accuracy of the radiator-perturber interaction, and the accuracy of the perturber correlations.…”
Section: Introductionmentioning
confidence: 99%